Multiple field tests on landing day: Early mobility may improve postural recovery following spaceflight - Rosenberg, Marissa J.; Reschke, Millard F.; Tomilovskaya, Elena S.; Wood, Scott J. (Frontiers in Physiology, 2022)
Adaptation to microgravity causes astronauts to experience sensorimotor disturbances during return to Earth leading to functional difficulties. Recently, the Field Test (FT) study involving an incrementally demanding sensorimotor functional test battery has allowed for an unprecedented view into early decrements and recovery from multiple tests conducted on the landing day following 6-months International Space Station missions. Although the protocol was challenging and temporarily increased motion sickness symptoms, there were anecdotal reports that performing these tasks within the first few hours of landing accelerated their recovery. Therefore, results from computerized dynamic posturography (CDP) following return to Houston were used to compare recovery between crewmembers that participated in FT (n = 18) with those that did not (controls, n = 11). While there were significant decrements in postural performance for both groups, some FT participants tended to perform closer to their preflight baseline in the most challenging condition of the CDP sensitive to vestibular function—eyes closed, unstable support and head movements. However, the distribution of difference scores appeared bimodal with other FT participants in the lower range of performance. We attribute these observations to the manner in which the field tests were implemented—some benefitted by encouraging early movement to drive adaptation when performed in a constrained incremental fashion; however, movements above aversive thresholds may have impaired adaptation in others. Challenging the sensorimotor system with increasingly provocative movements performed as close to landing as possible, as long as within individual thresholds, could be a useful intervention to accelerate astronaut’s sensorimotor readaptation that deserves further study.